Proceedings of the 20th ACM International Conference on Information and Knowledge Management 2011
DOI: 10.1145/2063576.2063638
|View full text |Cite
|
Sign up to set email alerts
|

What and how children search on the web

Abstract: The Internet has become an important part of the daily life of children as a source of information and leisure activities. Nonetheless, given that most of the content available on the web is aimed at the general public, children are constantly exposed to inappropriate content, either because the language goes beyond their reading skills, their attention span differs from grown-ups or simple because the content is not targeted at children as is the case of ads and adult content. In this work we employed a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…It has been widely reported (Craswell, Zoeter, Taylor, & Ramsey, ; Hua, Zhang, Liu, Ma, & Ru, ) that users tend to click on top‐ranked results even if these results do not contain the information that users are looking for. Duarte Torres and Weber () showed that this behavior is even stronger for younger users. The motivation behind using this restricted query set was to reduce this behavioral bias.…”
Section: Random Walk Evaluationmentioning
confidence: 94%
See 2 more Smart Citations
“…It has been widely reported (Craswell, Zoeter, Taylor, & Ramsey, ; Hua, Zhang, Liu, Ma, & Ru, ) that users tend to click on top‐ranked results even if these results do not contain the information that users are looking for. Duarte Torres and Weber () showed that this behavior is even stronger for younger users. The motivation behind using this restricted query set was to reduce this behavioral bias.…”
Section: Random Walk Evaluationmentioning
confidence: 94%
“…Similar age groups have been used in previous research on children's search behavior on the web and represent marked stages of child development (Duarte Torres & Weber, ). These groups were also selected because we can create models from the age ranges defined in the Dmoz directory.…”
Section: Data Set Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children tend to enter short, natural language queries, rather than using keywords or Boolean operators (Bilal & Kirby, 2002;Duarte Torres & Weber, 2011;Gossen, Low, & Nürnberger, 2011;Kammerer & Bohnacker, 2012;Marchionini, 1989;Solomon, 1993). Older studies indicated that children preferred browsing to keyword searching (Borgman, Hirsh, Walter, & Gallagher, 1995), but more recently, children have expressed a preference for keyword searching (Jochmann-Mannak, Huibers, Lentz, & Sanders, 2010); this may be because children are exposed to Google at a young age now.…”
Section: Children's Information Behaviorsmentioning
confidence: 99%
“…Such search portals are ostensibly designed to deliver safe, relevant information for novice Web users while supporting their cognitive and motor skills with child‐appropriate interfaces (Gossen, Hempel, & Nürnberger, ). Over the past 20 years, online searching for children has evolved from curated collections of materials in portal‐ and catalogue‐like interfaces to keyword‐based search engines that more closely approximate how adult tools look and function (see earlier work, e.g., Bilal, ; Druin et al, ; Duarte Torres & Weber, ; Schacter, Chung, & Dorr, ). What many of these search systems implicitly or explicitly acknowledged was the essential trade‐off of information quality and quantity in favor of safety.…”
Section: Introductionmentioning
confidence: 99%